EKSISTENSI NASKH SEBAGAI METODE PENYELESAIAN AYAT-AYAT KONTRADIKTIF PERSPEKTIF JASSER AUDA (Telaah QS Al-Taubah [9]: 5) - Muchammad Syarif Hidayatullah; Setio Budi (university Of islam, 2023)
The existence of the text theory has had such a big impact on the struggle of thoughts regarding the completion of verses which are considered to be very contradictory and cannot be compromised. They use the text theory as an alternative to resolve contradictory verses, one of which is Jasser Auda. This research will explain as well as answer the existence of the text from the perspective of Jasser Auda and its relation to QS al-Taubah [9]: 5) which is often considered to have written other verses, so this research is expected to provide solutions in addressing verses that are externally assessed contradictory. Using a type of qualitative research with library research (library research) holistically, the results of this study indicate that Jasser Auda is one of the contemporary thinkers who rejects texts in the Koran and its existence as a method in ta'āruḍ al-adillah based on several arguments built by him Therefore, Auda offers an alternative method, namely system analysis (systems approach) with an emphasis on the features of wholeness and multidimensionality features (religious thinking that involves various dimensions). By using the features offered by Auda, the conclusion drawn from the analysis of QS al-Taubah [9]: 5) is that this verse does not contradict other verses.